Prevalence and application of an evolving genome editing tool “CRISPR/Cas System” in cancer research and treatment - Shaikat, Mahdi Mubin (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2022.